2016
DOI: 10.1007/s11255-016-1389-6
|View full text |Cite
|
Sign up to set email alerts
|

Urinary L-FABP as a marker of vesicoureteral reflux in children: could it also have a protective effect on the kidney?

Abstract: Urinary liver-type fatty acid-binding protein was considered to be helpful for the diagnosis of vesicoureteral reflux, and also it might contribute to understand the mechanisms causing scar tissue formation especially for the patients who had vesicoureteral reflux. Further clinical and experimental investigations are required to elucidate in detail the physiology of liver-type fatty acid-binding protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Several studies have proved that L-FABP is a promising biomarker of various kidney diseases as type 2 diabetes, vesicoureteral reflux, and B12 deficiency [21][22][23]. In the current study, urinary L-FABP was significantly higher in T1D subjects than in controls and also in the diabetic group it was significantly higher in microalbuminuric than in normoalbuminuric diabetic subjects.…”
Section: Discussionsupporting
confidence: 61%
“…Several studies have proved that L-FABP is a promising biomarker of various kidney diseases as type 2 diabetes, vesicoureteral reflux, and B12 deficiency [21][22][23]. In the current study, urinary L-FABP was significantly higher in T1D subjects than in controls and also in the diabetic group it was significantly higher in microalbuminuric than in normoalbuminuric diabetic subjects.…”
Section: Discussionsupporting
confidence: 61%
“…This matter makes them obese, and the high BMI index is a known risk factor for lower levels of response to hepatitis B vaccine. [ 15 16 17 18 29 30 ] This explanation may be the probable reason for the lower levels of response to the hepatitis B vaccine in students of our study and those of other countries. Baba Mahmoodi[ 29 ] reported that smoking and obesity had negative effects on the production of antibodies after vaccination with hepatitis B.…”
Section: Discussionmentioning
confidence: 67%
“…Low levels of response to hepatitis B vaccine in students with higher levels of BMI is maybe due to the distribution of vaccine in fat not in muscle which decrease its absorption. Significant effects of age and BMI on the levels of response to hepatitis B vaccine have been reported from Belgium,[ 15 ] China,[ 16 ] Turkey,[ 17 ] and Iran. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…The proposed option for the cure of this disease and to make blood flow better is to use a bioengineered vein (silver microchannel) in the varicose vein. There are similar examples of stent implantation [ 82 , 83 , 84 , 85 ]. The bioengineered blood vessel also appears to be safe for dialysis process.…”
Section: Resultsmentioning
confidence: 99%